Improving treatment of women with schizophrenia: a review of the recent literature - Alexandre González-Rodríguez; Jesús Cobo; Mary V. Seeman (Open Exploration Publishing Inc., 2023)
Effective clinical management of women with schizophrenia is therapeutically challenging. While there have been recent advances in the understanding of neurobiological, hormonal, and female reproductive cycle factors that play a decisive role in the development and progression of schizophrenia in women, this knowledge has not yet been fully translated into treatment practice. The aim was to apply the best evidence available to optimally treat women with schizophrenia at various periods of the lifespan. A narrative review was conducted of recent advances (2018-2023) in aspects of schizophrenia in women that demand sex-specific treatment. Sex steroids impact antipsychotic absorption, distribution, metabolism, elimination, passage through the blood-brain barrier, and blood flow rate to the brain. For these reasons, premenopausal women with schizophrenia, as compared to male age peers, require lower doses of most antipsychotic drugs and suffer comparatively more adverse events (metabolic, sexual, and cardiovascular) at similar doses. Apart from pharmacologic treatment, women have specific reproductive planning needs and need protection from sexual exploitation and domestic abuse. In addition, when pregnant, schizophrenia women show a high risk of gestational diabetes and pre-eclampsia/eclampsia that requires prevention. Prevention is also needed against long-term health hazards for their offspring. Another period of therapeutic challenge specific to women is menopause. The collected evidence points to women-specific recommendations for both biological and psychosocial treatment strategies for schizophrenia.